Perceraian Pada Perkawinan Usia Dini (Studi Di Desa Rumbuk) - Sri Hariati; Musakir Salat (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The purpose of this study was to determine the causes of early marriage and the reasons for underage divorce. The formulation of the problem is: 1. What causes early marriage in Rumbuk village. 2. What is the reason for divorce in early marriage in Rumbuk village. The research method used is empirical research method. get or have a more established life, low education factor due to lack of income of parents who cannot afford to pay for school, as well as juvenile delinquency factor who can't hold back which results in getting pregnant out of wedlock. 2. Things that cause divorce are economic factors and psychological factors. Economic factors are driven by the absence of employment opportunities so that a family head cannot meet the daily needs of his family. Meanwhile, psychologically, early marriage can cause trauma and a crisis of self-confidence and emotions that do not develop properly